2011
DOI: 10.1002/mrm.23101
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid prospective and retrospective head motion correction to mitigate cross‐calibration errors

Abstract: Utilization of external motion tracking devices is an emerging technology in head motion correction for MRI. However, cross-calibration between the reference frames of the external tracking device and the MRI scanner can be tedious and remains a challenge in practical applications. In this study, we present two hybrid methods, which both combine prospective, optical-based motion correction with retrospective entropy-based autofocusing in order to remove residual motion artifacts. Our results revealed that in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 26 publications
(55 reference statements)
4
82
0
1
Order By: Relevance
“…While most of the previous investigations performed the RMC method for rigid motion correction in k -space and some in spatial domain [29][30][51][52], this work demonstrated that the RMC method can be successfully utilized for non-rigid motion correction of bladder MR imaging in the spatial domain. Since the motion correction in the k -space can only effectively compensate for rigid motions, such as: translation, rotation, expansion, and general affine, it is not desired to use direct correction method for non-rigid motions in the k -space.…”
Section: Conclusion and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While most of the previous investigations performed the RMC method for rigid motion correction in k -space and some in spatial domain [29][30][51][52], this work demonstrated that the RMC method can be successfully utilized for non-rigid motion correction of bladder MR imaging in the spatial domain. Since the motion correction in the k -space can only effectively compensate for rigid motions, such as: translation, rotation, expansion, and general affine, it is not desired to use direct correction method for non-rigid motions in the k -space.…”
Section: Conclusion and Discussionmentioning
confidence: 89%
“…al. , [30] divided the k-space into several segments and considered the motion by individually correcting for the rotation and translation of each segment via minimizing an entropy-based auto-focusing criterion. Sharper edges in the final image were observed after the motion correction.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we should recall that our technique admits a straightforward combination with these sort of approaches. Namely, if we assume motion can be well approximated by using external sensors, we would be in a more favorable regime to perform further small-motion adjustments (for instance to mitigate cross-calibration errors [25]). Also, provided motion can be accurately estimated and k-space sampling can be assumed homogeneous enough, our retrospective reconstruction would have a negligible impact in the image quality, which would reduce the need to perform real time modifications to the acquisition sequence.…”
Section: Discussionmentioning
confidence: 99%
“…For rigid body motion these are described according to the Fourier theorems: a translation of the object leads to a phase ramp in the acquired k-space, an object rotation corresponds to a rotation of k-space (113). While translations are relatively easy to correct by applying a phase change to the acquired data, the correction of rotations requires the use of non-Cartesian reconstruction methods (114,115) and includes some sophisticated algorithms (116-119) which are computationally intensive.…”
Section: Artefact Mitigation Strategiesmentioning
confidence: 99%